Activatable fluorescent probes for hydrolase enzymes based on coumarin–hemicyanine hybrid fluorophores with large Stokes shifts. Issue 42 (16th April 2020) - Fujioka, Hiroyoshi; Uno, Shin-nosuke; Kamiya, Mako; Kojima, Ryosuke; Johnsson, Kai; Urano, Yasuteru
Abstract : We show that the equilibrium of intramolecular spirocyclization of coumarin–hemicyanine hybrid fluorophores can be finely tuned by means of chemical modifications to develop activatable fluorescence probes for hydrolases with large Stokes shift. Abstract : We show that the equilibrium of intramolecular spirocyclization of coumarin–hemicyanine hybrid fluorophores can be finely tuned by means of chemical modifications. We used this scaffold to develop activatable fluorescent probes with large Stokes shifts for γ-glutamyltranspeptidase and esterase.